2020
DOI: 10.7150/ijms.46707
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin attenuates Salivary Hypofunction through the Prevention of Oxidative Stress in Human Submandibular Gland Cells

Abstract: Xerostomia (dry mouth) is a significant age-related condition. Meanwhile, cordycepin, the natural therapeutic agent, has demonstrated an anti-aging effect. Therefore, the present study aimed to investigate the preventive effects of cordycepin on secretory function in an in vitro model of hydrogen peroxide (H 2 O 2 )-induced salivary hypofunction. After being exposed to H 2 O 2 , human submandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…We noted 45 papers claiming that the cytotoxic effect of cordycepin at bioactive concentrations was low. We noted the highest concentration which promoted cell survival or did not cause statistically significant cell death in these papers and determined the median and the range [ 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 69 , 70 , 80 , 95 , 98 , 102 , 105 , 106 , 117 , 142 , 145 , 164 , 184 , 240 , 270 , 301 , 315 , 317 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 ].…”
Section: Methodsmentioning
confidence: 99%
“…We noted 45 papers claiming that the cytotoxic effect of cordycepin at bioactive concentrations was low. We noted the highest concentration which promoted cell survival or did not cause statistically significant cell death in these papers and determined the median and the range [ 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 69 , 70 , 80 , 95 , 98 , 102 , 105 , 106 , 117 , 142 , 145 , 164 , 184 , 240 , 270 , 301 , 315 , 317 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 ].…”
Section: Methodsmentioning
confidence: 99%
“…AQP5 is a water channel protein located in salivary gland acinar cells that mediates transcellular water movement. (32)(33)(34) Muscarinic receptor stimulation also induces translocation of AQP5 from the cytoplasm to the apical side of the acinar cells. (35) Previous studies reported that an antioxidant found in green tea and some plant-derived compounds promote salivation via AQP5 translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Real-Time Quantitative PCR HSG cells (Jaiboonma et al, 2020) were seeded in 6-well plates with a DMEM containing 1% FBS. The cells were stimulated with apigenin (0.01, 0.1, and 1 μM) and E2 (0.1 μM) for 48 h. The total RNA from differently treated cells was extracted using a total RNA extraction reagent.…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%